An introduction to multi-stakeholder partnerships - Stibbe, Darian; Prescott, Dave (The Partnering Initiative, 2016)
This briefing document for the GPEDC High Level Meeting in November 20 16 offers a definition of multi-stakeholder partnerships (MSPs) and sh ows how they are being used, where they have come from, and what the d ifferent sectors bring to the table. It provides an overview of the ch allenges the present, what they require from individuals and organisat ions, and how they get started. The report was written with the suppor t of the PEP Initiative, and funded by the Netherlands Ministry of For eign Affairs.